Faculty and International Engagement: Has Internationalization Changed Academic Work? - Proctor, Douglas (International Higher Education, 2015)
Internationalization is increasingly seen as comprehensive, with international strategies now touching on all aspects of a higher education institution’s activity. In this light, it is assumed that faculty play a key role in the internationalization of their institution. Yet, little is known about the extent to which faculty consider international activities or international engagement an important aspect of their work, and whether internationalization has changed understandings of what it means to be an academic in higher education today.